(untitled) (Baghdad Science Journal, 2021)
The concepts of higher Bi- homomorphism and Jordan higher Bi- homomorphism have been introduced and studied the relation between Jordan and ordinary higher Bi- homomorphism also the concepts of Co- higher Bi- homomorphism and Co- Jordan higher Bi- homomorphism introduced and the relation between them in Banach algebra have also been studied.